Impact of coach education on coaching effectiveness in youth sport: A systematic review and meta-analysis - Li, L.; Olson, H. O.; Tereschenko, I.; Wang, A.; McCleery, J. (International Journal of Sports Science & Coaching, 2025)
Sport plays a crucial role in the health and wellbeing of young people. While positive outcomes from sports participation are often assumed, studies show that these depend significantly on coaches` attitudes and behaviors, which shape the sporting environment and influence participants` experiences and outcomes. This study provides a systematic review with meta-analysis of various coach education program interventions (CEPIs), aiming to answer the question: How do CEPIs impact coaching effectiveness compared to standard coaching practices without such programs? Analyzing a total of 45 studies (N = 180,658), this systematic review is divided into a narrative section followed by a meta-analysis. Positive effects of CEPIs were observed in 78% of the studies, seen in coaches` knowledge gain, attitude shifts, and behavioral changes, as well as in athletes` physical and psychological outcomes, both within and outside of sport. Overall, a significant moderate to large effect of CEPIs on coaching effectiveness (g = 0.47, k = 264, 95% CI [0.36, 0.59]) was noted. Specifically, a large overall effect on coach outcomes (g = 0.73, k = 71, 95% CI [0.47, 1.00]) and a moderate to large overall effect on athlete outcomes (g = 0.38, k = 193, 95% CI [0.28, 0.47]) were observed. These findings generally support the positive impact of CEPIs on coaching effectiveness across the reviewed studies. However, the effects varied in magnitude, scalability, and sustainability for coaches and athletes. The discussion focuses on insights derived from CEPIs and future improvement strategies.